PHYSIOLOGICAL EFFECTS OF RESVERATROL AND COUMARIC ACID ON TWO MAJOR GROUNDNUT PESTS AND THEIR EGG PARASITOID BEHAVIOR. Issue 4 (18th February 2016) - Sambangi, Pratyusha; Rani, Pathipati Usha
Abstract : Groundnut, Arachis hypogea L., is one of the plant species that synthesizes phenolic compounds, resveratrol and coumaric acid. They are induced as a defense strategy in plant in response to feeding lepidopterans. The present study investigated the role of resveratrol and coumaric acid in producing antiherbivore effects as a direct defense against two major groundnut pests, Spodoptera litura F. and Amsacta albistriga W., and in indirect defense by attracting the egg parasitoid Trichogramma chilonis Ishii under laboratory conditions. The phenolic compounds deterred the feeding of both pests and caused reduction in the larval weights in a dose‐dependent manner in leaf disk bioassays. Antioxidant mechanisms of larvae fed with these phenols were measured by estimating the activities of superoxide dismutase (SOD), ascorbate peroxidase (APOX), and catalase (CAT). Enzyme activities increased significantly in experimental larvae, more so in resveratrol‐treated than in coumaric acid treated larvae. Feeding larvae with resveratrol and coumaric acid resulted in enhanced activities of detoxifying enzymes, carboxyl esterase (EST), and glutathione‐S‐transferase (GST) in the midgut tissues of both species, indicating the toxic nature of these compounds. Trichogramma chilonis was more attracted toward coumaric acid treatments in Y‐olfactometer tests than to resveratrol. This study contributes to the understanding of the roles of resveratrol and coumaric acid in direct as well as indirect defense, we infer a possible utilization of these compounds in alternate measures of groundnut pest control in future.